COMMUNICABLE DISEASE SURVEILLANCE IN POST-FLOOD SETTINGS: LESSONS FROM THE LITERATURE - Landi, Soleman; Wahyuni, Maria Magdalena Dwi; Niron, Maissie Ginaninta Charoline; Loe, Wahyunita Euniche Elizabeth; Tabun, Kornelia; Huky, Stella Elsha Putri Rihi; Sabakodi, Dwi Andika Umbu Gauka; Dimu, Rivaldo Deljunior (JURNAL WIDYA MEDIKA, 2026)
Floods are natural disasters that frequently occur in Indonesia and contribute to an increased risk of communicable diseases due to environmental changes, poor sanitation, and limited access to clean water. This study aims to describe communicable diseases surveillance after floods based on findings from various studies in Indonesia. The method used was a literature review by searching for relevant scientific articles through the Google Scholar and PubMed databases for publications from 2018 to 2025. The articles included were selected based on topic relevance, availability of full text, and relevance to communicable diseases surveillance after flooding. The results of the study show that the most common communicable diseases that emerge after flooding include diarrhea, acute respiratory infections, dermatitis, dengue fever, leptospirosis, malaria, typhoid fever, and measles. The increase in cases of these diseases is related to water source contamination, damage to sanitation facilities, temporary housing density, and the formation of puddles that support the development of disease vectors. This study also shows that vulnerable groups, especially toddlers and the elderly, as well as productive age groups with high levels of environmental exposure, are at greater risk of contracting diseases after flooding. Integrated health surveillance, supported by public education and the implementation of Clean and Healthy Living Behaviors (PHBS), plays an important role in the early detection of increased cases, strengthening health responses, and controlling communicable diseases after flooding in affected areas.